Proses Pemberdayaan Masyarakat Desa Sitimulyo Kecamatan Piyungan Kabupaten Bantul Dalam Pembentukan Kelompok Pengelola Sampah Mandiri (KPSM) - Ambar Teguh Sulistyani; Yulia Wulandari (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2017)
Waste management generally is the responsibility of local government.“Kartamantul” cooperation of waste management in Yogyakarta, Sleman and Bantul, waste disposal is concentrated in TPSA (waste dump) Piyungan, particularly in Sitimulyo Village. The volume of the waste is increased which leads to the limitation of TPSA capacity. Recently, government has been experiencing difficulty to provide waste dump facility. In this critical period, the participation of college institution to deliver its sollution and devotion is highly required. Universitas Gadjah Mada, as one of college institutions that concerns to problem raised in environment, has carried out society empowerment. Through action research methodology and data collection technique of direct participative observation, interview, documentation, and focus group discussion can arrange action plan. UGM team along with the society continuously performs experiments until KPSM has professional to produce both solid and liquid organik fertilizer. The intensity of education, consultation, and mentoring has resulted in KPSM capacity enhancement. Pioneering program in environment and household waste management is the opening to the development of “Sitimulyo” organik fertilizer. Besides organik fertilizer produced with organik waste is used by local community, it also has been sold to consumer.